2014
DOI: 10.3390/ijerph110707163
|View full text |Cite
|
Sign up to set email alerts
|

Parent-Child Associations in Pedometer-Determined Physical Activity and Sedentary Behaviour on Weekdays and Weekends in Random Samples of Families in the Czech Republic

Abstract: This study investigates whether more physically active parents bring up more physically active children and whether parents’ level of physical activity helps children achieve step count recommendations on weekdays and weekends. The participants (388 parents aged 35–45 and their 485 children aged 9–12) were randomly recruited from 21 Czech government-funded primary schools. The participants recorded pedometer step counts for seven days (≥10 h a day) during April–May and September–October of 2013. Logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(76 citation statements)
references
References 60 publications
(144 reference statements)
4
67
1
4
Order By: Relevance
“…Although there is no published research regarding the number of children that participate in after school activities, or the types of those activities, it is known that children in Greece take part in at least one organized movement programme, such as football, basketball, dance, or gymnastics. Regarding gender PA differences, previous research findings are conflicting, with some researchers reporting similar ambulatory activity for both genders (1,2) and others revealing that boys are more active than girls (19,20,29). In the present study, boys were found to have higher ambulatory activity than girls, however, both presented low levels of PA, a finding that is in line with the study of Kambas et al (2).…”
Section: Children Parentssupporting
confidence: 85%
See 4 more Smart Citations
“…Although there is no published research regarding the number of children that participate in after school activities, or the types of those activities, it is known that children in Greece take part in at least one organized movement programme, such as football, basketball, dance, or gymnastics. Regarding gender PA differences, previous research findings are conflicting, with some researchers reporting similar ambulatory activity for both genders (1,2) and others revealing that boys are more active than girls (19,20,29). In the present study, boys were found to have higher ambulatory activity than girls, however, both presented low levels of PA, a finding that is in line with the study of Kambas et al (2).…”
Section: Children Parentssupporting
confidence: 85%
“…Boys (n = 29) Girls (n = 29) Fathers (n = 25) Mothers (n = 33) tigate potential associations between them. The results revealed that children were significantly more active on weekdays than at the weekend, a finding that is confirmed in several previous studies (2,19,26). In Greece, only one study (2) focusing on preschoolers' ambulatory activity had been conducted before this one, in which children accumulated 9,191 steps/day on weekdays and 7,913 steps/day at the weekend.…”
Section: Children Parentssupporting
confidence: 81%
See 3 more Smart Citations